KUALITAS PELAYANAN PUBLIK DALAM PEMBUATAN KARTU INDENTITAS ANAK (KIA) - Fernandes Yudha; Firman Firdausi (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Public service which still relatively low, seen from the many complaints and complaints of the community either directly or through mass media and facilities and infrastructure that is still not adequate. This problem also occurs in Kota Batu about the quality of public services recently issued by the government, such as in the Minister of Home Affairs Regulation No. 2 Year 2016 About About Child Identity Card (KIA). This study aims to determine the Quality of Public Service in the Making of Identity Card of Children. This research esed qualitative method. Data collection techniques use observation, interview and documentation. The result of the research is known the Quality of Public Service in making the Identity Card of Child given by the Office of Population and Civil Registration of Batu City in accordance with the requirements / demands in order to fulfill the public satisfaction and free from deficiency / damage. Efforts to improve the quality of public services in accordance with the basic rules and procedures that have been defined such as Simplify service with no convoluted, Openness of information service, equitable justice and Completeness of Facilities and Infrastructure that still needs to be improved. With Thus the effort to improve the quality of public services already at the stage of improvement / workmanship with obstacles that need to be improved. Keywords: Quality, Public Services, child ID card Abstrak: Pelayanan Publik yang masih tergolong rendah dilihat dari banyaknya keluhan dan pengaduan masyarakat baik secara langsung maupun melalui media massa serta sarana dan prasarana yang masih belum memadai. Persoalaan ini juga terjadi di Kota Batu tentang kualitas pelayanan publik yang baru diterbitkan oleh pemerintah, seperti dalam Peraturan Mentri Dalam Negeri No 2 Tahun 2016 Tentang Tentang Kartu Identitas Anak (KIA). Penelitian ini bertujuan untuk mengetahui Kualitas Pelayanan Publik Dalam Pembuatan Kartu Identitas Anak. Metode Penelitian yang digunakan Kualitatif. Teknik pengumpulan data dengan cara pengamatan, wawancara dan dokumentasi. Hasil penelitian diketahui Kualitas Pelayanan Publik Dalam Pembuatan Kartu Identitas Anak yang diberikan oleh Dinas kependudukan Dan Pencatatan Sipil Kota Batu sesuai dengan persyaratan/tuntutan demi memenuhi kepuasan masyarakat serta bebas dari kekurangan/kerusakan. Upaya meningkatkan kualitas pelayanan publik sesuai dengan aturan pokok dan tata cara yang telah ditetapkan seperti Menyederhanakan pelayanan dengan tidak berbelit-belit, Keterbukaan akan informasi pelayanan, keadilan yang merata serta Kelengkapan Sarana dan Prasarana yang masih perlu diperbaiki. Dengan Demikian upaya meningkatkan kualitas pelayanan publik sudah pada tahap peningkatan/pengerjaannya dengan hambatan yang perlu diperbaiki. Kata Kunci : Kualitas, Pelayanan Publik, Pembuatan Kartu Identitas Anak